Water sensitive urban design for the karst zone of Bacalar, Quintana Roo, Mexico - Ibarra-Marigal, Silvana Marisa; Hernández-Montero, Yesenia Nayrovick; Nahuat-Sansores, Javier Rodrigo; Rejón-Parra, David Gustavo; Sánchez-Quijano, Miguel Ángel; Mena-Rivero, Roberto; Torrescano-Valle, Nuria; Arellano-Guillermo, Alfredo; Romero-Martínez, Ángel Iván (Ecosistemas y Recursos Agropecuarios, 2022)
In the karst regions of Mexico, the construction of cities has been carried out using materials and processes that do not correspond to the functioning of filtration dynamics. The present work analyzes the effects of WSUD (Water Sensitive Urban Design) implementation on karst zone and the influence in the reduction of flooding. A permeability model was developed for the urban area of Bacalar, Quintana Roo, Mexico. As a first phase, precipitation, runoff, and infiltration were modeled; the useful infrastructure to maintain the connectivity of the hydrological system was determined and permeability models considering different scenarios were generated. In the second phase, the efficiency of the model scenarios was analyzed. Finally, flood damages were assessed for each scenario. The results show that if 68% of the urban area is kept permeable and 32% impermeable with sponge infrastructure, with a return period of 10 years, the onset of flooding is delayed by up to 30 minutes. This implies a saving of 5.56 million minimum wages. The implementation of DUSA reduces flooding, generates social and economic savings, but also maintains the flow dynamics and connectivity of the karst. The international DUSA model reduces the vulnerability of karst systems to climate change.
Keywords: Climate change, flooding, urban modeling, permeability, economic valuation